Cellular aspects of immunity involved in the development of atherosclerosis - Khalaf, Khalil; Chamieh, Marc; Welc, Natalia; Singh, Chandpreet; Kaouk, Joanne Lynn; Kaouk, Aiden; Mackiewicz, Andrzej; Kaczmarek, Mariusz; Perek, Bartlomiej (Frontiers in Immunology, 2025)
Atherosclerosis, previously regarded as a lipid storage disease, has now been classified as a chronic inflammatory disease. The hardening of arterial vessels characterizes atherosclerosis due to the accumulation of lipids in the arterial walls, eliciting an inflammatory response. The development of atherosclerosis occurs in various stages and is facilitated by many clinical factors, such as hypertension, hyperlipidemia, and inflammatory status. A large arsenal of cells has been implicated in its development. This review will summarize the phases of atherosclerotic formation and all the cells involved in either promoting or inhibiting its development.